Crônicas dos jovens na periferia : criminalização da pobreza, sociabilidades e conflitos - Oliveira, Daniela Cristina Neves de (2018)
This paper discusses the sociabilities and intersubjective conflicts between adolescents and young people in the periphery of Vitória-ES. Since the 1980s, adolescents and young people (in general, Afro-descendants and males) constitute the group most victimized by homicides in Brazil. In this sense, it is the segment most exposed to violent situations. In view of these things, we take a step back from the iniquitous picture of juvenile homicides to reflect on the meanings of conflicts between adolescents and young people in the light of the dynamics of sociability. The research intends to move from the macro context to the micro analysis, as well as shifting the focus from homicide studies to conflict studies. Nonetheless, from the macro analysis point of view, I examine the criminalization aspect of poor urban youth, which has historical roots in this society. However, the main goal is to reflect "what do people do with what they do to them?". That is, the intention is to empirically observe the relationship between structural constraints and how individuals act in their field of possibilities, from the meanings they attribute to things in their daily lives. I start from a qualitative approach, which uses as narrative life instruments and focus group, as well as participant observation and questionnaires with open questions. I focused on individuals aged 14 to 26 years, who were fulfilling a socio-educational measure of detention in the scope of the Institute of Socioeducational Assistance of Espírito Santo and subjects with the same age profile, but residents of peripheral neighborhoods of Vitória, notably the neighborhood region São Pedro. Among the meanings analyzed in relation to conflicts, I highlight the social construction of masculinity and the moral rules of conduct defined by the groups to regulate coexistence. In a given context, conflicts and, in the limit, homicides are legitimated morally, by virtue of the perception that one lives in a state of "war" in which others are "enemies." As a result, intragroup and intragroup mistrust probably supports the use of violence. The aforementioned context concerns sociability in the retail trade of illicit substances, spread throughout the impoverished neighborhoods of the Região Metropolitana da Grande Vitória, which fosters a culture or an agonistic way of being. Finally, I emphasize that in the same socioeconomic context there are different forms of youth sociability. Therefore, since I compare two groups, I try to understand which are the conditioning factors for the differentiality of life paths, especially when it comes to engaging in (risky) illegal activities. These factors are basically related to the family and school context and other spheres of sociability (such as social projects and churches) from which the agents participate, constituting meanings that guide their decisions.